Inclusion Through Innovation: Online Learning in Higher Education - Harprayudi, Aryo Dwi; Lantu, Donald Crestofel; Sushandoyo, Dedy (Ridwan Institute, 2025)
This research investigates both the opportunities and limitations of online learning as a means to broaden access to business education in developing countries. Although online platforms are often viewed as scalable tools for expanding educational reach, numerous structural and pedagogical challenges continue to hinder their overall effectiveness. Using a systematic literature review, this study compiles insights from recent academic publications and organizes them within a conceptual framework based on input-process-impact logic. It draws upon the Unified Theory of Acceptance and Use of Technology (UTAUT), various learning theories, and Bloom’s Taxonomy to assess how online learning is adopted, how learning unfolds, and what outcomes it produces. Major obstacles include inadequate digital infrastructure, lack of tailored teaching approaches, low student engagement, and concerns about long-term financial viability. Nevertheless, the study emphasizes the long-term promise of online learning in promoting educational and digital inclusion, especially when driven by thoughtful design, strong institutional support, and enabling policy. The research offers practical guidance for educators, policymakers, and academic institutions working to build more inclusive and impactful online learning environments within the business education landscape.